2020
DOI: 10.1002/chem.202003815
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline Photobasicity: Investigation within Water‐Soluble Light‐Responsive Copolymers

Abstract: Quinoline photobases exhibit a distinctly higher p K a in their electronically excited state than in the ground state, thereby enabling light‐controlled proton transfer reactions, for example, in molecular catalysis. The absorption of UV light translates to a p K a jump of approximately 10 units, as established for small‐molecule photobases. This contribution presents the first synthesis of quinoline‐based polymeric photobases prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(32 reference statements)
0
7
0
2
Order By: Relevance
“…[54] For example, several studies concerning quinoline photobasicity have shown an increase in approximately 10 pK a units for quinoline derivatives exposed to UV light. [54,83] In particular, the excited states of the studied quinoline photobases are of sufficient energy to facilitate proton transfer from the reaction media (e.g., water or alcohols), which yields the conjugate base upon irradiation with an appropriate excitation wavelength (Figure 4b). The mechanism for generation of conjugate bases proceeds through abstraction of a proton from a hydrogen-bonded donor.…”
Section: Photoacids and Photobasesmentioning
confidence: 99%
“…[54] For example, several studies concerning quinoline photobasicity have shown an increase in approximately 10 pK a units for quinoline derivatives exposed to UV light. [54,83] In particular, the excited states of the studied quinoline photobases are of sufficient energy to facilitate proton transfer from the reaction media (e.g., water or alcohols), which yields the conjugate base upon irradiation with an appropriate excitation wavelength (Figure 4b). The mechanism for generation of conjugate bases proceeds through abstraction of a proton from a hydrogen-bonded donor.…”
Section: Photoacids and Photobasesmentioning
confidence: 99%
“…[54] So haben beispielsweise mehrere Studien zur Photobasizität von Chinolin einen Anstieg des pK a -Wertes um circa 10 Einheiten bei Chinolinderivaten gezeigt, die UV-Licht ausgesetzt waren. [54,83] Insbesondere haben die angeregten Zustände der untersuchten Chinolin-Photobasen eine ausreichende Energie, um den Protonentransfer aus den Reaktionsmedien (z. B. Wasser oder Alkohole) zu erleichtern, wodurch bei Bestrahlung mit einer geeigneten Anregungswellenlänge die konjugierte Base entsteht (Abbildung 4b).…”
Section: Photosäuren Und Photobasenunclassified
“…Separate experiments are needed to establish that a thermodynamically possible proton transfer process is also kinetically feasible. Previous work by us and others have demonstrated that quinolines are indeed kinetically competent for proton capture from a variety of proton donors. , The idea of Förster cycle analysis is, of course, general and has been employed to explain other excited-state processes before, including for metal–ligand interactions. , …”
Section: Conceptsmentioning
confidence: 99%